Clinico–pathological features, treatments and survival of malignant insulinomas: a multicenter study. Issue 4 (April 2020) - Veltroni, A; Cosaro, E; Spada, F; Fazio, N; Faggiano, A; Colao, A; Pusceddu, S; Zatelli, M C; Campana, D; Piovesan, A; Pia, A; Grossrubatscher, E M; et al.
Abstract : Introduction: Management of malignant insulinomas is challenging due to the need to control both hypoglycaemic syndrome and tumor growth. Literature data is limited to small series. Aim of the study: To analyze clinico-pathological characteristics, treatments and prognosis of patients with malignant insulinoma. Materials and methods: Multicenter retrospective study on 31 patients (male: 61.3%) diagnosed between 1988 and 2017. Results: The mean age at diagnosis was 48 years. The mean NET diameter was 41 ± 31 mm, and 70.8% of NETs were G2. Metastases were widespread in 38.7%, hepatic in 41.9% and only lymph nodal in 19.4%. In 16.1% of the cases, the hypoglycaemic syndrome occurred after 46 ± 35 months from the diagnosis of originally non-functioning NET, whereas in 83.9% of the cases it led to the diagnosis of NET, of which 42.3% with a mean diagnostic delay of 32.7 ± 39.8 months. Surgical treatment was performed in 67.7% of the cases. The 5-year survival rate was 62%. Overall survival was significantly higher in patients with Ki-67 ≤10% ( P = 0.03), insulin level <60 µU/mL ( P = 0.015) and in patients who underwent surgery ( P = 0.006). Peptide Receptor Radionuclide Therapy (PRRT) was performed in 45.1%, with syndrome control in 93% of patients. Conclusions: Our study includes the largest series of patients with malignant insulinoma reported to date. The hypoglycaemic syndrome may occur after years in initially non-functioning NETs or be misunderstood with delayed diagnosis of NETs. Surgical treatment and Ki67 ≤10% are prognostic factors associated with better survival. PPRT proved to be effective in the control of hypoglycaemia in majority of cases.